A new approach for composite coating development on metallic materials - Maleque, Md. Abdul; Paijan, Lailatul Harina; Abdullah, Muhammad Azwan; Jamal, Nur Ayuni Jamal (2018)
A novel composite coated metallic material is invented based on single phase ceramic reinforcement and hybridization of composite coating using simple and cost effective TIG torch melting technique. This strategy provides better tribological behaviour of coated material even at higher temperature. Salient features of the product are: - Advanced lubrication concept Good metallurgical bonding Higher hardness Good wear resistanve (higher durability) Stable frictional control at high temperature